Application of the Modified Incremental Step Test for Pulmonary Rehabilitation. Issue 5 (1st February 2021) - Burge, Angela T; Rodrigues Jr, Jose C; Abramson, Michael J; Cox, Narelle S; Bondarenko, Janet; Webb, Elizabeth; Marceau, Tunya; Handley, Emma; Macdonald, Heather; Askin, Annabel; Calasans, Georgia A Santos Araújo; do Amaral, Daniel Pereira; et al.
Abstract: Objective: A Modified Incremental Step Test (MIST) performed in the home may facilitate entirely home-based pulmonary rehabilitation programs. The aims of this study were to investigate the reliability and responsiveness, and the utility of the MIST for exercise prescription in people with stable chronic lung disease. Methods: The MIST was undertaken at the center and home in random order, before and after pulmonary rehabilitation, with 2 tests at each time point. Reliability was assessed using intraclass correlation coefficient. Responsiveness was evaluated as effect size. The minimal important difference was appraised using distribution and anchor-based methods. In a substudy, physiological responses to MIST were measured by a portable metabolic system, followed by a constant step rate test at 60% of peak oxygen uptake (VO2 peak), to evaluate utility for exercise prescription. Results: Forty-six participants were recruited (29% of eligible candidates). There was excellent reliability for number of steps recorded in home- and center-based settings (intraclass correlation coefficient = 0.954, 95% CI = 0.915–0.976). A small-moderate effect size was demonstrated following pulmonary rehabilitation (0.34), and the minimal detectable change was 7 steps. All participants in the substudy achieved 60% of VO2 peak and achieved steady state by the fourth minute, with 60% of VO2 peak corresponding to a mean 37% (95% CI = 29–44) of the MIST final level. Conclusions: The MIST is reliable and responsive to pulmonary rehabilitation in people with stable chronic respiratory disease. It provides new opportunities to assess exercise capacity, prescribe exercise training, and reassess exercise program outcomes in environments where established field walking tests are not feasible. Impact: Pulmonary rehabilitation is a highly effective treatment that is underutilized worldwide. Home-based pulmonary rehabilitation may improve access for patients and deliver equivalent clinical outcomes but is limited by the availability of a robust exercise test that can be used at home to assess exercise capacity and prescribe training intensity. This study tested the clinimetric properties of the MIST and demonstrated a new way to assess exercise capacity, prescribe exercise training of an appropriate intensity, and reassess exercise capacity in environments where established field walking tests are not feasible.